2015
DOI: 10.1007/s12036-015-9321-5
|View full text |Cite
|
Sign up to set email alerts
|

Solar Magnetic Flux Ropes

Abstract: The most probable initial magnetic configuration of a CME is a flux rope consisting of twisted field lines which fill the whole volume of a dark coronal cavity. The flux ropes can be in stable equilibrium in the coronal magnetic field for weeks and even months, but suddenly they loose their stability and erupt with high speed. Their transition to the unstable phase depends on the parameters of the flux rope (i.e., total electric current, twist, mass loading etc.), as well as on the properties of the ambient co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 137 publications
6
28
0
Order By: Relevance
“…Our resulting magnetic field also shows a certain separation between the flux rope axis and top most dips as suggested by cavity observations (Hudson et al 1999;Régnier et al 2011;Gibson 2015;Filippov et al 2015;Su et al 2015;Bak-Steslicka et al 2016). This is due to the curved geometry of the flux rope.…”
Section: Resultssupporting
confidence: 79%
“…Our resulting magnetic field also shows a certain separation between the flux rope axis and top most dips as suggested by cavity observations (Hudson et al 1999;Régnier et al 2011;Gibson 2015;Filippov et al 2015;Su et al 2015;Bak-Steslicka et al 2016). This is due to the curved geometry of the flux rope.…”
Section: Resultssupporting
confidence: 79%
“…Using New Solar Telescope (NST) observations, Wang et al (2015) also found that a set of loops developed into a flux rope before a two-ribbon flare. Filippov et al (2015) presented several filaments with highly twisted magnetic structure observed by the Transition Region And Coronal Explorer (TRACE) and Big Bear Solar Observatory (BBSO). These observations reveal that flux ropes may be ubiquitous in the solar atmosphere (Zhang et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…In our interpretation of these observations we follow the flux-rope model (e.g., Canou & Amari 2010;Guo et al 2010;Joshi et al 2014b;Filippov et al 2015) of filaments, considering filament plasma accumulated in lower parts of helical flux tubes. Dextral filaments are contained within the left-handed helices, while sinistral filaments fill the righthanded ones.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…The interaction of two nearby filament channels with different filament chiralities within a large-scale coronal fanspine magnetic structure have not been observed before, although fan-spine configurations have been discussed in the case of solar eruptions in "pseudostreamers" (Wang et al 2007;Török et al 2011b;Rachmeler et al 2014;Yang et al 2015), jets (Filippov et al 2009(Filippov et al , 2015Pariat et al 2009), and flares Joshi et al 2015).…”
Section: The Observations As Well As the Pfss Calculations Clearlymentioning
confidence: 99%